Nosocomial infections caused by bacteria of Enterobacteriacae family in cancer clinic - N. V. Dmitrieva; V. V. Aginova; I. N. Petukhova; Z. V. Grigorievskaya; А. I. Dmitrieva; N. S. Bagirova; I. V. Tereshchenko; Е. N. Khmaladze (Сибирский онкологический журнал, 2019)
The purpose of the study was to analyze the prevalence of multidrug-resistant (MDR) pathogens (Escherichia coli and Klebsiella pneumonia) isolated from cancer patients. material and methods. 862 strains of E. coli and 1 461 strains of K. pneumoniae isolated from wound, blood, urine and other pathological materials from cancer patients treated at N.N. Blokhin National Medical Research Center of Oncology (Moscow) between 2014 and 2016 were analyzed. results. Over the last 3 years, there has been a significant increase in the number of E.coli resistant to piperacillin-tazobactam (from 8.1 to 25 %), ceftriaxone (from 15.7 to 100 %), ertapenem (from 8.1 to 97.7 %), and amikacin (c 4.5 to 14.6 %). The number of E. coli producing carbapenemases has increased from 5.8 to 20.8 % (p≤0.0001). Among K. pneumoniae, a significant increase in the number of strains resistant to piperacillin-tazobactam (from 59.7 to 89.7 %), ceftazidime (from 62.8 to 82.8 %), ceftriaxone (from 62.8 to 100 %), cefepime (from 63.1 to 83.8 %), ertapenem (from 62.1 to 100 % ), imipenem (from 30.0 to 81.0 %), and meropenem (from 53.9 to 86.8% ) is observed. conclusion. Evaluation of the frequency of isolation of MDR microorganisms over time is an essential element of epidemiological surveillance and is necessary for the correct treatment of patients with infectious complications.